Increased risk of cardiovascular disease (CVD) with age in HIV‐positive men: a comparison of the D:A:D CVD risk equation and general population CVD risk equations. Issue 10 (19th May 2014) - Petoumenos, K; Reiss, P; Ryom, L; Rickenbach, M; Sabin, CA; El‐Sadr, W; d'Arminio Monforte, A; Phillips, AN; De Wit, S; Kirk, O; Dabis, F; Pradier, C; et al.
Abstract : Objectives: The aim of the study was to statistically model the relative increased risk of cardiovascular disease (CVD) per year older in Data collection on Adverse events of anti‐HIV Drugs (D:A:D) and to compare this with the relative increased risk of CVD per year older in general population risk equations. Methods: We analysed three endpoints: myocardial infarction (MI), coronary heart disease (CHD: MI or invasive coronary procedure) and CVD (CHD or stroke). We fitted a number of parametric age effects, adjusting for known risk factors and antiretroviral therapy (ART) use. The best‐fitting age effect was determined using the Akaike information criterion. We compared the ageing effect from D:A:D with that from the general population risk equations: the Framingham Heart Study, CUORE and ASSIGN risk scores. Results: A total of 24 323 men were included in analyses. Crude MI, CHD and CVD event rates per 1000 person‐years increased from 2.29, 3.11 and 3.65 in those aged 40–45 years to 6.53, 11.91 and 15.89 in those aged 60–65 years, respectively. The best‐fitting models included inverse age for MI and age + age 2 for CHD and CVD. In D:A:D there was a slowly accelerating increased risk of CHD and CVD per year older, which appeared to be only modest yet was consistently raised compared with the risk in the general population. The relative risk of MI with age was not different between D:A:D and the general population. Conclusions: We found only limited evidence of accelerating increased risk of CVD with age in D:A:D compared with the general population. The absolute risk of CVD associated with HIV infection remains uncertain.